PELESTARIAN LINGKUNGAN PESISIR LAUT KAWASAN PPLH PUNTONDO: PENANAMAN BIBIT MANGROVE - Anisa; Thahir, Rahmatia; Magfirah, Nurul; Baharullah, Baharullah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
Community service activities, namely planting mangrove seedlings aimed at preserving the marine environment in the PPLH Puntondo area. This activity consists of two stages, namely (1) Cleaning the marine coastal area of PPLH Puntondo; (2) planting mangrove seedlings in the marine coastal area of PPLH Puntondo. This activity is located at points on the PPLH Puntondo sea coast which are experiencing damage and death of mangroves. The implementation team together with PPLH Puntondo and local residents have succeeded in planting 200 mangrove seedlings. Mangroves have a very important role for coastal ecosystems. The survival of marine life on the coast is very dependent on mangroves. Therefore, mangrove planting activities on the sea coast of PPLH Puntondo are carried out to preserve mangroves and the survival of marine life.